THE PROBLEMS OF HUMAN TRAFFICKING AS TRANSNATIONAL CRIMES IN THE PERSPECTIVE OF IMMIGRATION AND INTERNATIONAL LAW - Respati Triana Putri; Felix Ferdin Bakker; Dhea Chairunnisa (Journal of Law and Border Protection, 2022)
Globalization on an international scale has an impact on progress in the fields of information technology, communication, and transportation, making borders between countries depleted or borderless. This has become a principle in the international legal order, especially regarding the concept of state sovereignty. Every country in various parts of the world has been guaranteed in international law and has the exclusive right to exercise the sovereignty of its country without being able to be intervened by other countries or any party. The sovereignty of a country is an absolute thing that cannot be ignored, because sovereignty is a sign of an independent and sovereign country. International migration that occurs has a positive impact, but sometimes creates a new problem. Like Human Trafficking or human trafficking. The author will discuss Human Trafficking in the perspective of immigration and international law, including the function of immigration as a government agency that oversees the traffic of people in and out of Indonesian territory in order to maintain state sovereignty. This research itself is based on juridical and empirical normative research, namely by elaborating each material followed by observing the study of existing policies and regulations. This is intended so that this crime, namely human trafficking, can be elaborated with existing national and international legal policies and from an immigration perspective.